Effects of air pollution caused by sugarcane burning in Western Sao Paulo on the cardiovascular system - Silva Pestana, Paula Roberta da [UNESP]; Ferreira Braga, Alfesio Luis; Cipulo Ramos, Ercy Mara [UNESP]; Oliveira, Ariadna Ferraz de; Osadnik, Christian Robert; Ferreira, Aline Duarte [UNESP]; Ramos, Dionei [UNESP] (Revista De Saude Publica, 2017)
OBJECTIVE: To evaluate the effects of acute exposure to air pollutants (NO2 and PM10) on hospitalization of adults and older people with cardiovascular diseases in Western Sao Paulo. METHODS: Daily cardiovascular- related hospitalization data (CID10 - 100 to 199) were acquired by the Department of Informatics of the Brazilian Unified Health System (DATASUS) from January 2009 to December 2012. Daily levels of NO2 and PM10 and weather data were obtained from Companhia Ambiental do Estado de Sao Paulo (CETESB - Sao Paulo State Environmental Agency). To estimate the effects of air pollutants exposure on hospital admissions, generalized linear Poisson regression models were used. RESULTS: During the study period, 6,363 hospitalizations were analysed. On the day of NO2 exposure, an increase of 1.12% (95% CI 0.05- 2.20) was observed in the interquartile range along with an increase in hospital admissions. For PM10, a pattern of similar effect was observed; however, results were not statistically significant. CONCLUSIONS: Even though with values within established limits, NO2 is an important short- term risk factor for cardiovascular morbidity.